Evaluation of properties and biodeterioration’s potential of polyethylene and aliphatic polyesters blends - Machado, A. V. (2007)
Blends of high density polyethylene (HDPE) and biodegradable polymers - polylactic acid, PLA, poly(ε-caprolactone), PCL and Mater-Bi|Superscript|®|/Superscript| (thermoplastic starch (TPS) with PLA or PCL) - were prepared in a co-rotating twin-screw extruder, together with polyethylene modified with maleic anhydride (PE-g-MA) used as compatibiliser. The mechanical and rheological properties, morphology and potential for biodeterioration of polymeric materials were evaluated. Blends with PLA showed a reduced elongation at break but an increased Young's modulus while the addition of PCL led to materials with a greater elongation at break and a lower Young modulus. The rheological results evidenced that HPDE and the blend with the highest TPS level exhibited the highest viscosity. The microbial growth test carried out to evaluate the potential for biodeterioration of the blends, using a pure culture of Pseudomonas fluorescens, indicated that HDPE/PCL had a lower resistance to bacterial attack than the blend of HDPE/PLA. This was verified by a higher cell number on its surface after 10 weeks of incubation. The addition of 30% starch to the HDPE/PLA blend enhanced its biodeterioration potential, the same was not observed in the case of the HDPE/PCL blend containing just 18% starch.